A strategy for human resources management in enterprises (Economics and region, 2019)
The essence of modern problems in the field of human resource management is revealed. It is proved that the development of personnel strategy and its implementation allow the company to improve the efficiency of personnel use. There are formed the stages of formation of strategic personnel management. The directions of the implementation of management activities for the effective formation and use of personnel potential are developed. The authors proposed a general concept for developing a personnel management strategy for an enterprise. As a result of the research, it was established that the methods of forming the strategy for managing the personnel potential of an enterprise should be based on the active use of modern opportunities. Effective personnel policy in the system of strategic personnel management is one of the tools for managing business processes.
Keywords: personnel; enterprise; personnel potential; strategic management; personnel strategy; personnel management